Knowledge, Attitude, and Performance of Dentists toward Dental Treatments during Corona Pandemic: A Review Article - Heidari, Leila; Sadeghipour, Maryam; Arshadi fard, Baharan; Soleimanpoor, Sarvin (Journal of Dental School, 2024)
Objectives On December 11, 2019, the World Health Organization declared the outbreak of the new coronavirus (COVID-19). The rapid transmission of the COVID-19 virus through aerosols in the air and on contaminated surfaces highlights the increased importance of personal hygiene. By April 7, 2023, approximately 684 million people worldwide had contracted the virus, with over 6 million lives lost. This survey summarizes dentists' knowledge, attitude, and performance during the COVID-19 pandemic. Methods A keyword search was conducted in April 2023 on Google Scholar and PubMed databases. The search results for MeSH words such as awareness, attitude, performance, dentist, COVID-19, and self-care yielded 24 articles published from 2019 to 2023. Nine articles were excluded from the study for not addressing one of the 3 knowledge, attitude, and performance (KAP) factors. Results This study analyzed a total of 15 articles. The results were organized in three categories: knowledge, attitude and performance. Generally, dentists in these studies had a good knowledge about COVID-19 but based on most studies continuous education in this field is necessary. Regarding attitude and performance, studies showed that most of dentists prefer to perform only emergency procedures using personal protective equipment. Conclusion Dentists included in these studies generally demonstrated an acceptable level of knowledge, attitude and performance about COVID-19.